The effect of distress tolerance to the process on substance use in individuals with substance use disorders - Bahadır, Erdi; Güneş, Ferruh; Noyan, Cemal Onur (Journal of Dependence, 2019)
Objective: Substance use disorder affects individuals and communities alloverthe world and continues to create a growing danger. In this study, the effect of tolerance to distress on substance use in people with substance use disorder was investigated. Method: In this study, 50 people were admitted to NP Brain Hospital and 4 of them were female and 46 were male. The question naire was applied to the participants, including sociodemographic data form, Tolerating Distress Scale and Subtance Craving Scale. Results: The correlation analysis showed that there was a negative, moderate, and significant correlation between Substance Craving Scale and Tolerating Distress Scale and its subscales. Participants with a low level of tolerance for distress were found to have a high level of Subtance Craving Scale medians. Before and after the treatment, there was a significant difference for the median of the participants’Subtance Craving Scale and Tolerating Distress Scale. 50% of the participants who post-treatment distress tolerance lewel is low were using the substance again and 20% of the participants who post-treatment distress tolerance lewel is high were using the substance again. Conclusion: The findings of the study show that the level of tolerance of distress has an effect on the substance use process.